Cross-serial dependencies are not hard to process - VOGEL, CARL (My University, 1996)
Crossserial dependencies in Dutch and SwissGerman are the only known extra context free natural language syntactic phenomena Psycholinguistic evidence suggests crossserial orderings tend to be easier to process than nested construc tions We argue that the expressivity re quirements of the corresponding formal languages do not actually entail that pro cessing reduplication languages require the worstcase time complexity for lan guages of the same expressive class We distinguish between contextfree repre sentability and contextfree processing We show that for any language with up to context free expressive power pro cessing crossserial dependencies can be accommodated without aecting parsing complexity This is related to other work on reduplication phenomena in formal models of computation
PUBLISHED
Keywords: Computer Science